The NOK/euro exhange rate after inflation targeting: The interest rate rules - Roger Bjørnstad; Eilev S. Jansen (Statistics Norway, Research Department, 2007)
Norway adopted a flexible inflation target in March 2001 following a long period with exchange rate targeting in various forms. The regime shift reverses the causal ordering between changes in the nominal exchange rate and changes in the interest rate. When the central bank targets the exchange rate, interest rates are rarely changed independently of foreign interest rates and only to counteract large movements in the exchange rate after interventions have failed to stabilise the exchange rate. With inflation targeting the interest rate is used to stabilise the domestic economy and has a strong impact on the exchange rate. The long run (steady state) relationship between the interest rate and the exchange rate is on the other hand not altered by the change in monetary policy regime. This means that the fundamental equilibrating mechanism - that is the PPP condition augmented with a risk premium - remains the same across regimes.
Keywords: C51; C52; C53; E42; F31; 330; monetary policy regime shift; NOK/euro exchange rate; role of interest rates; equilibrium real exchange rate; purchasing power parity; uncovered interest parity